Comparison of CVT Performance with the Manual and Automatic Transmission for Evaluation the Fuel Consumption and Exhaust Emissions - Jawad, Qahtan Adnan; Ali, Abdulbaqi K. (Basrah Journal for Engineering Sciences, 2020)
Continuously Variable Transmission (CVT) combines the efficiency of manual transmissions with the driving comfort of automatic transmissions while providing an infinite range of gear ratios, improved fuel economy, and enhanced acceleration performance. This study presents a comparative evaluation of CVT performance against manual and automatic transmissions in a parallel hybrid electric vehicle (HEV), focusing on fuel consumption and exhaust emissions. A baseline HEV model equipped with a CVT gearbox was selected from ADVISOR simulation software and subsequently modified by replacing the CVT with manual and automatic transmissions for comparison. Exhaust emissions, including catalytic converter pollutant reactions, were recorded for all configurations. Performance assessments were conducted using several global standard driving cycles to simulate real driving conditions. Results indicated that the CVT configuration achieved superior fuel economy and a significant reduction in exhaust emissions compared with manual and automatic transmissions. This improvement is attributed to the CVT’s effective control of speed ratio and overall transmission efficiency. The findings support the suitability of CVT gearboxes for urban hybrid vehicle applications due to their low fuel consumption and high efficiency in speed ratio control.